An Image Processing Technique for Determining Missing dots in Half Tone Multi-coloured Prints - Verikas, A. (Elektronika ir Elektrotechnika, 1998)
This paper presents an image processing technique for determining the amount of missing dots in half tone multi-coloured prints. Two methods for solving the problem are presented. The first method is based on the least squares technique, while the second one involves calculation of the city block distance transform. The first method determines the exact number and place of missing dots in an observed area. It requires, however, the printed dots to be approximately regularly distributed in the observed area. The second method does not count the number of missing dots, instead, it estimates the percentage of an observed area where density of the dots is less than an observed average. The second method is more robust and general.